Analisis Faktor-Faktor yang Berhubungan dengan Brand Image Rumah Sakit - Diana Rachmania; Dhina Widayati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Maintaining a positive image in the eyes of the public is one way that customers remain loyal to re-select the hospital when customers need health services. The factors that related to brand image are physical factors (packaging, logo, brand name) and psychological factors (trust, value, personality), quality, reliability, benefits and price. The purpose of this study was to determine the factors related to Hospital’s Brand Image where the factors studied were the quality of hospital service, physical condition of the hospital’s building and hospital’s tariff. Methods: The design of this research was correlational by using cross sectional approach. Sample amounted to 30 taken by purposive sampling technique. Data were collected using structured questionnaire and were then analyzed using Spearman's rho with level of significance α <0.05Results: The result of this research indicate that quality of hospital’s service factor (p value = 0,001), physical condition of hospital building (p value = 0, 003) and hospital tariff (p value = 0,001) related to Hospital’s Brand ImageConclusion: the hospital needs to pay attention to factors that can affect the brand image in order to make the image of hospital better and the customer remains loyal to use the hospital as an option when they need health services.